Revolutionizing Tourism: Harnessing the Power of IoT in Smart Destinations - Farid, Smail; Boudia, Mohamed Ayoub; Mwangi, Grace (Tecno Scientifica Publishing, 2023)
The convergence of technology and travel has given rise to the paradigm of smart destinations, fueled by the transformative force of the Internet of Things (IoT). This review paper delves into the revolutionary impact of IoT on tourism, specifically focusing on the concept of smart destinations. Smart Hotels, exemplifying this paradigm shift, redefine the guest experience through seamless technology integration. Smart room controls, driven by IoT, intuitively respond to guest preferences, transforming the traditional stay into a personalized and efficient encounter. Transportation undergoes a parallel transformation through connected transportation, where IoT innovations reshape global mobility. From smart airports to intelligent traffic management systems, the integration of IoT ensures seamless and efficient travel experiences for both passengers and goods. Wearable devices further enhance the tourism experience, with smart tour guides leading the way. Wearables provide real-time information and personalized recommendations, with smart glasses employing augmented reality (AR) to overlay digital information onto the physical world. This hands-free approach enriches tourist exploration of historical sites and museums. In popular tourist attractions, IoT-enabled experiences redefine engagement. From smart museums to AR tours and interactive exhibits, the integration of IoT technologies enhances how visitors interact with cultural landmarks, creating immersive and technologically enriched tourism experiences. This review explores the multifaceted intersections of IoT and tourism, offering insights into current trends and future prospects in this dynamic space.